Pattern Of Skin Diseases In A Rural Village Development Community Of Nepal - Shrestha, R; Shrestha, DP; Lama, L; Gurung, D; Rosdahl, I (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
<!--[if gte mso 9]> 72 <![endif]--> Introduction: Skin diseases are a common cause of morbidity in Nepal as per the health services report. There is limited information on the prevalence and pattern of skin diseases in the community. The objective of this study was to determine the pattern of skin diseases in a rural village development community of Nepal. Materials and methods: Two dermatologic health camps were conducted, during which, the villagers were examined by dermatologists. The skin diseases diagnosed were recorded in a proforma. Results: There were 433 individuals examined and 359 (male-47.9%; female-52.1%) had skin disease identified clinically (camp prevalence- 83%). The age of patients ranged from 1 to 80 years (mean-24.5; SD±15.9), with majority in the age group of 10-19 years. The most common skin disease category was eczemas (36.4%), followed by infections (28.4%), acne (22%), pigment disorders (34%) and urticaria (12.3%). Conclusion: Skin diseases were common in the community. The five most common Skin disease categories were eczemas, infections, acne and pigment disorders were the more common conditions. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10595 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014 pp.41-44